Impure Public Goods and Technological Interdependencies - Dirk T.G. Rübbelke; Andreas Löschel (Fondazione Eni Enrico Mattei (FEEM), 2005)
Impure public goods represent an important group of goods. Almost every public good exerts not only effects which are public to all but also effects which are private to the producer of this good. What is often omitted in the analysis of impure public goods is the fact that regularly these private effects can also be generated independently of the public good. In our analysis we focus on the effects alternative technologies independently generating the private effects of the public good may have on the provision of impure public goods. After the investigation in an analytical impure public good model, we numerically simulate the effects of alternative technologies in a parameterized model for climate policy in Germany.
Keywords: H41; C61; Q53; Q54; 330; Impure public goods; Climate policy; Rationing; Öffentliches Gut; Klimaschutz